Analisa Quality Of Work Life (QWL) dan Motivasi terhadap Kepuasan Kerja Karyawan - Novita Wahyu Setyawati; Serin Latukau; Dewi sri woelandari PG; Tyna yunita (Cakrawala Management Business Journal, 2020)
This study aims to analyze the quality of work life (QWL) of employee job satisfaction with motivation as a moderating variable at PT. Infomedia Solusi Humanika Jakarta. This research uses quantitative research methods, with data collection techniques through interviews, questionnaires and literature study. The number of samples in this study were 100 respondents who were employees of PT. Infomedia Solusi Humanika Jakarta. Tests used to test the research instruments are validity, reliability, classic assumption tests, and hypothesis testing to find out whether Ha is accepted or Ho is rejected. The results of this study indicate that: (1) Quality of work life (QWL) has a positive and significant effect on job satisfaction of employees of PT. Infomedia Solusi Humanika Jakarta. Thus the better the quality of work life (QWL), the better the job satisfaction of its employees. (2) Motivation does not act as a moderating variable that affects the relationship of quality of work life (QWL) with employee job satisfaction at PT. Infomedia Solusi Humanika Jakarta. This is possible for other variables that affect the quality of work life (QWL) with job satisfaction such as discipline, leadership, and compensation.